Law Enforcement Against Narcotics Crime Recidivists - Rezkiansyah Rahmat Paneo (Estudiante Law Journal, 2020)
This article aims to find out the effectiveness of law enforcement against narcotics crimes recidivists. Based on the title raised in this study, the researcher used empirical research methods. The process of collecting data from the object studied in this study was by using interview techniques, document studies, and observation techniques. As for law enforcement against narcotics crime recidivists by the Resort Police Gorontalo CIty, they have carried out their duties with procedures, especially in handling narcotics cases with the aim that the community, especially narcotics case recidivists, does not recur, but based on the results of research from the author, it is concluded that handling narcotics cases, especially for the recidivists were still not effective. Keywords: Law Enforcement, Recidivists, Narcotics